Motor Maps, Seizures, and Behaviour. - Teskey, G. Campbell; Monfils, Marie H.; Flynn, Corey; Young, Nicole A.; Van Rooyen, Francine; Henry, Luke C.; Ozen, Lana J.; Henderson, Amy K.; Reid, Aylin Y.; Brown, Andrew R. (Canadian Journal of Experimental Psychology, 2008)
Atypically organised motor maps have been described in some people with epilepsy and we have modelled this in rats. Our goal is to more fully understand the mechanisms responsible for seizure-induced functional brain reorganisation and to reverse their effects. Here we present an overview- of the relationship between neocortical motor maps, seizures, and interictal behaviour. To begin we summarise the observations of atypical motor maps with epilepsy and in animal models following experimentally induced seizures. Our novel experiments have established that motor map expansion is linked to a functional alteration of motor behaviour. Evidence for some of the putative brain mechanisms responsible for motor map size is discussed. Our successes reversing seizure-induced map expansion by two different methods are also briefly reviewed. Lastly, unanswered questions for possible future experimentation are posed. Reprinted by permission of the publisher.